A display panel and display device

CN122962848APending Publication Date: 2026-10-23XIAMEN TIANMA MICRO ELECTRONICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611150111.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

但是,目前采用低阻偏光片的液晶显示装置存在稳定性和信赖性不足的问题,例如在车载显示领域,液晶显示装置在高温高湿等严苛的信赖性测试中会出现肉眼可见的腐蚀缺陷,甚至进入显示区,影响产品的显示效果和良率

Benefits of technology

本发明提供的显示面板中,通过在银胶的导电银粉设计导电层,使所述银胶在具有优良的导电性能的同时,有效抑制了高温高湿等苛刻环境下的银离子迁移,避免银离子与偏光片中的碘离子发生反应而导致的腐蚀问题,从而解决了液晶显示装置在湿热环境下的信赖性问题,使所述显示面板具有更高的耐湿热稳定性和信赖性,提升产品的显示品质和良率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122962848A_ABST
    Figure CN122962848A_ABST
Patent Text Reader

Abstract

The application provides a display panel and a display device, the display panel comprising an array substrate, a color filter and a polarizer, the color filter being located between the array substrate and the polarizer, and the polarizer being electrically connected with the array substrate through silver adhesive; the silver adhesive comprises conductive silver powder, and the conductive silver powder comprises silver powder and a conductive layer coated on the surface of the silver powder. By designing a conductive layer on the conductive silver powder of the silver adhesive, the silver adhesive has excellent conductivity, and the migration of silver ions under harsh environments such as high temperature and high humidity is effectively inhibited, the corrosion problem caused by the reaction between silver ions and iodine ions in the polarizer is avoided, and thus the reliability problem of the liquid crystal display device under a humid heat environment is solved, the display panel has higher humidity and heat resistance and reliability, and the display quality and yield of the product are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of liquid crystal display technology, specifically relating to a display panel and a display device. Background Technology

[0002] Liquid crystal displays (LCDs) offer advantages such as being radiation-free, thin and light, and energy-efficient, leading to their widespread use in various information, communication, and consumer electronics products. Existing LCDs typically include a high-resistivity film located between the polarizer and the liquid crystal array substrate. This film primarily dissipates static electricity generated by finger touches, cover plate friction, etc., preventing the accumulation of static charge within the display panel and thus avoiding display defects. However, the fabrication process for the high-resistivity film is complex, with high raw material and equipment costs. Large-area fabrication also suffers from poor uniformity, making it prone to localized failures. Furthermore, it increases the overall thickness of the panel, hindering the pursuit of thinner and lighter panel products.

[0003] To address the shortcomings of high-resistivity films, the industry has developed low-resistivity polarizers. These polarizers integrate anti-static functionality and form conductive paths with silver paste, thus replacing high-resistivity films. However, current liquid crystal display devices using low-resistivity polarizers suffer from insufficient stability and reliability. For example, in automotive displays, visible corrosion defects can occur during stringent reliability tests involving high temperature and humidity, even penetrating the display area and affecting display quality and yield. Therefore, solving the reliability issues of liquid crystal display devices in harsh environments such as humidity and heat, and developing display devices with excellent resistance to humidity and heat stability and reliability, is a key research focus in this field. Summary of the Invention

[0004] To address the reliability issues of liquid crystal display devices in harsh environments such as humidity and heat, and to develop display devices with excellent resistance to humidity and heat and high reliability, one objective of this invention is to provide a display panel comprising an array substrate, a color filter, and a polarizer. The color filter is located between the array substrate and the polarizer, and the polarizer and the array substrate are electrically connected by silver paste. The silver paste comprises conductive silver powder, and the conductive silver powder comprises silver powder and a conductive layer coated on the surface of the silver powder.

[0005] In the display panel provided by this invention, the polarizer and the array substrate are electrically connected by silver paste. The conductive silver powder in the silver paste includes silver powder and a conductive layer coated on its surface. The design of the conductive layer gives the conductive silver powder and silver paste high conductivity, enabling them to perform excellent electrical connection. On the other hand, the conductive layer has a barrier function, which can effectively inhibit the migration / deposition of silver ions in the conductive silver powder under harsh environments such as high temperature and high humidity. This avoids the corrosion problem caused by the reaction of silver ions with iodine ions in the polarizer, significantly improving the humidity and heat resistance stability of the display panel and giving it higher reliability.

[0006] A second objective of this invention is to provide a conductive silver paste, wherein the conductive silver paste comprises the following components in parts by weight: 40-60 parts of conductive silver powder 10-20 parts of polymer carrier Solvent 10-40 parts; The conductive silver powder includes silver powder and a conductive layer coated on the surface of the silver powder.

[0007] The second objective of this invention is to provide a method for preparing the conductive silver paste described in the second objective, the method comprising: mixing conductive silver powder, polymer carrier and solvent uniformly to obtain the conductive silver paste.

[0008] A fourth objective of the present invention is to provide a display device comprising a display panel as described in one objective.

[0009] Compared with the prior art, the present invention has at least the following beneficial effects: The display panel provided by this invention features a conductive layer designed with conductive silver powder in the silver paste. This design ensures that the silver paste has excellent conductivity while effectively inhibiting the migration of silver ions under harsh environments such as high temperature and high humidity. This prevents corrosion caused by the reaction of silver ions with iodine ions in the polarizer, thereby solving the reliability problem of liquid crystal display devices in humid and hot environments. The resulting display panel exhibits higher stability and reliability in humid and hot conditions, improving the display quality and yield of the product. Attached Figure Description

[0010] Figure 1 This is a schematic diagram of the structure of a display device during the research process of this invention; Figure 2 This is a schematic diagram illustrating the penetration corrosion problem of a display device during the research process of this invention; Figure 3 This is a partial structural diagram of a display panel provided in one embodiment of the present invention; Figure 4A This is a partial structural schematic diagram of a display panel provided in another embodiment of the present invention; Figure 4B This is a partial structural schematic diagram of a display panel provided in another embodiment of the present invention; Figure 5 This is a partial structural schematic diagram of a display panel provided in another embodiment of the present invention; Figure 6 EDS test image of the conductive silver powder provided in Example 2 of this invention; Figure 7A A schematic diagram of the structure of conductive silver powder provided in a specific embodiment of the present invention; Figure 7B A schematic diagram of the structure of conductive silver powder provided in another specific embodiment of the present invention; Figure 7C A schematic diagram of the structure of conductive silver powder provided in another specific embodiment of the present invention; Figure 7D A schematic diagram of the structure of conductive silver powder provided in another specific embodiment of the present invention; Figure 7E A schematic diagram of the structure of conductive silver powder provided in another specific embodiment of the present invention; Figure 7F A schematic diagram of the structure of conductive silver powder provided in another specific embodiment of the present invention; Figure 8 This is an aging verification test diagram of a display panel provided in an embodiment of the present invention; Figure 9 The aging verification test diagram of the display panel is provided for comparison. Detailed Implementation

[0011] To facilitate understanding of the present invention, specific embodiments are provided to further illustrate the technical solution of the present invention. Those skilled in the art should understand that the embodiments are merely illustrative of the present invention and should not be considered as specific limitations thereof.

[0012] In this invention, features specified as "first" and "second" may explicitly or implicitly include one or more of these features, used to distinguish and describe features, without any order or emphasis. In the description of this invention, unless otherwise stated, "multiple" means two or more.

[0013] The terms “comprising,” “including,” “having,” “containing,” or any other variations thereof, as used herein, are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not limited to those elements and may also include other elements not expressly listed or elements inherent to such composition, step, method, or article.

[0014] "Optional" or "any one" means that the matter or event described thereafter may or may not occur, and the description includes both the possibility that the event may occur and the possibility that the event may not occur.

[0015] The indefinite articles “a” and “an” preceding an element or component of this invention do not impose any limitation on the quantity (i.e., number of occurrences) of the element or component. Therefore, “an” or “a” should be interpreted as including one or at least one, and the singular form of an element or component also includes the plural form, unless the quantity clearly refers only to the singular form.

[0016] In this invention, the terms "upper," "lower," "inner," "outer," "vertical," and "horizontal," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. They should not be construed as limitations on this invention.

[0017] In this invention, unless otherwise explicitly specified and limited, terms such as "connected," "linked," "installed," and "fixed" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. Those skilled in the art can understand the specific meanings of the above terms within this invention according to the specific circumstances.

[0018] like Figure 1 As shown, Figure 1 This is a schematic diagram of the structure of a display device during the research process of this invention. The display device typically includes an array substrate (Array) 10, a color filter (CF) 20, and a low-resistance polarizer (low-resistance POL) 30A. The low-resistance polarizer 30A includes a polarizer body 31A and a low-resistance pressure-sensitive adhesive layer (low-resistance PSA) 32A. The low-resistance pressure-sensitive adhesive layer 32A is located between the color filter 20 and the polarizer body 31A. The low-resistance polarizer 30A and the array substrate 10 are connected by a silver paste structure 40A to form a conductive path.

[0019] This invention, through research, has discovered that the low-resistivity polarizer 30A is currently mainly composed of iodine-based PVA material, which contains a complex formed by iodine-based dyes and PVA (polyvinyl alcohol). The material contains iodide ions (including I3). - and / or I5 - ); Silver paste structure 40A will release Ag in harsh environments such as high temperature and high humidity. + It reacts with iodine ions in the low-resistivity polarizer 30A to form... Figure 2 The image shows a penetration corrosion problem. For example, in applications with strict reliability requirements, such as automotive displays, the penetration corrosion of low-resistivity polarizers can even penetrate into the display area, forming visible defects that affect the product's reliability, display effect, and yield.

[0020] To address the aforementioned technical problems, embodiments of the present invention provide a display panel and a display device comprising the same. A specific conductive silver powder is used in the silver paste, comprising silver powder and a conductive layer coated on its surface. This allows the silver paste to possess excellent conductivity while effectively suppressing silver ion migration under harsh environments such as high temperature and high humidity. It also prevents the penetration corrosion problem caused by the reaction of silver ions with iodine ions in the polarizer, thus solving the reliability problem of the liquid crystal display device in humid and hot environments. This results in the display panel having higher resistance to humid and hot conditions and greater reliability, improving the display quality and yield of the product.

[0021] To make the above-mentioned objects, features, and effects of the present invention more apparent, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be noted that the drawings of the present invention are not necessarily drawn to scale.

[0022] like Figure 3 As shown, Figure 3 This is a partial structural diagram of a display panel provided in one embodiment of the present invention. The display panel includes an array substrate 10, a color filter 20, and a polarizer 30. The color filter 20 is located between the array substrate 10 and the polarizer 30. The polarizer 30 and the array substrate 10 are electrically connected by a silver paste 40. The silver paste 40 includes conductive silver powder, and the conductive silver powder includes silver powder and a conductive layer coated on the surface of the silver powder.

[0023] In the display panel provided by this invention, the polarizer 30 and the array substrate 10 are electrically connected by a silver paste 40. The silver paste 40 uses conductive silver powder as a conductive filler and includes silver powder and a conductive layer coated on the surface of the silver powder. The conductive layer plays a conductive role, giving the conductive silver powder and the silver paste 40 excellent conductivity and forming a conductive path between the polarizer 30 and the array substrate 10. On the other hand, the conductive layer has chemical inertness and barrier properties, which can effectively inhibit the migration and precipitation of silver ions in the conductive silver powder under harsh environments such as high temperature and high humidity, thereby avoiding the reaction between silver ions and iodine ions in the polarizer. This solves the problem of polarizer corrosion caused by penetration, significantly improves the humidity and heat resistance of the display panel, has higher reliability, and improves the display quality and yield of the product.

[0024] In the conductive silver powder of the present invention, the conductive layer does not impose any special limitation on the coating form / state of the silver powder. For example, the conductive layer may fully coat the surface of the silver powder or partially coat (half-coat) the surface of the silver powder; the conductive layer may be a flat coating or an uneven coating.

[0025] In some optional embodiments of the present invention, the material of the conductive layer includes any one or a combination of at least two of the following: metal, metal oxide, organic conductive material, and conductive carbon material.

[0026] In some optional embodiments of the present invention, the metal includes any one or a combination of at least two of Au, Ni, Cu, Al, and Fe, preferably any one or a combination of at least two of Au, Ni, and Cu.

[0027] In some optional embodiments of the present invention, the metal oxide includes any one or a combination of at least two of copper oxide, zinc oxide, silver oxide, indium tin oxide, indium zinc oxide, fluorine-doped tin oxide, and aluminum-doped zinc oxide.

[0028] In some optional embodiments of the present invention, the organic conductive material includes a conductive polymer and / or a conductive SAM (self-assembled monolayer) material, and more preferably any one or a combination of at least two of polyaniline (PANI), poly(3,4-ethylenedioxythiophene) / poly(4-styrenesulfonate) (PEDOT / PSS), polypyrrole (PPy), and conjugated conductive SAM.

[0029] In some optional embodiments of the present invention, the conductive carbon material includes any one or a combination of at least two of conductive graphite, graphene, carbon fiber, conductive carbon black, and carbon nanotubes.

[0030] In one specific embodiment, the structural schematic diagram of the conductive silver powder is shown below. Figure 7A and 7B As shown, the conductive layer 402 completely covers the silver powder 401, and the conductive layer 402 can be a flat coating ( Figure 7A ) or uneven covering ( Figure 7B Furthermore, in the embodiment of flat coating, the material of the conductive layer includes any one or a combination of at least two of metals and metal oxides; in the embodiment of uneven coating, the material of the conductive layer includes any one or a combination of at least two of organic conductive materials and conductive carbon materials.

[0031] In another specific embodiment, a schematic diagram of the conductive silver powder is shown below. Figure 7C , Figure 7D , Figure 7E , Figure 7F As shown, the conductive layer 402 partially or completely covers the silver powder 401, and the conductive layer 402 can be a flat coating. Figure 7C and Figure 7D ) or uneven covering ( Figure 7E and Figure 7F Furthermore, in the embodiment of flat coating, the material of the conductive layer includes any one or a combination of at least two of metals and metal oxides; in the embodiment of uneven coating, the material of the conductive layer includes any one or a combination of at least two of organic conductive materials and conductive carbon materials.

[0032] In some optional embodiments of the present invention, the thickness of the conductive layer is 1-150 nm, for example, it can be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm or 140 nm, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0033] In some optional embodiments of the present invention, the mass content of the conductive layer in the conductive silver powder is 0.5-39%, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, 32%, 34%, 35%, 36%, or 38%, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0034] In some optional embodiments of the present invention, the thickness and mass content of the conductive layer in the conductive silver powder can be adjusted according to the conductivity of the conductive layer material. For conductive layer materials with low resistivity and high conductivity, the thickness and mass content of the conductive layer can be higher to more effectively coat the silver powder, fully exert the barrier effect, and inhibit the migration and precipitation of silver ions. For conductive layer materials with relatively high resistivity and relatively low conductivity, the thickness and mass content of the conductive layer are lower so that while inhibiting the migration / precipitation of silver ions, the conductivity of the conductive silver powder and the silver paste are also taken into account.

[0035] In some optional embodiments of the present invention, the conductive silver powder satisfies at least one of the following conditions (1)-(4): (1) The material of the conductive layer is metal, and the thickness of the metal conductive layer in the conductive silver powder is 80-120 nm, for example, it can be 82 nm, 85 nm, 88 nm, 90 nm, 92 nm, 95 nm, 98 nm, 100 nm, 102 nm, 105 nm, 108 nm, 110 nm, 112 nm, 115 nm or 118 nm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific point values ​​included in the range.

[0036] In some optional embodiments of the present invention, the mass content of the metal conductive layer in the conductive silver powder is 23.5-38%, for example, it can be 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36% or 37%, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0037] (2) The material of the conductive layer is a metal oxide, and the thickness of the metal oxide conductive layer in the conductive silver powder is 1.5-3 nm, for example, it can be 1.6 nm, 1.8 nm, 2 nm, 2.2 nm, 2.4 nm, 2.5 nm, 2.6 nm or 2.8 nm, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0038] In some optional embodiments of the present invention, the mass content of the metal oxide conductive layer in the conductive silver powder is 1.8-3.6%, for example, it can be 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, 3%, 3.2%, 3.4% or 3.5%, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0039] (3) The material of the conductive layer is an organic conductive material. The thickness of the organic conductive layer in the conductive silver powder is 5-25 nm, for example, it can be 6 nm, 8 nm, 10 nm, 12 nm, 14 nm, 15 nm, 16 nm, 18 nm, 20 nm, 22 nm or 24 nm, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0040] In some optional embodiments of the present invention, the mass content of the organic conductive layer in the conductive silver powder is 4.6-20.5%, for example, it can be 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16%, 18% or 20%, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0041] (4) The material of the conductive layer is conductive carbon material, and the thickness of the conductive carbon material conductive layer in the conductive silver powder is 1-5 nm, for example, it can be 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm or 4.5 nm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific point values ​​included in the range.

[0042] In some optional embodiments of the present invention, the mass content of the carbon material conductive layer in the conductive silver powder is 0.8-2.4%, for example, it can be 0.9%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2% or 2.3%, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0043] In some alternative embodiments of the present invention, the silver paste further includes a polymer carrier comprising a combination of a first resin and a second resin, wherein the elastic modulus of the first resin is greater than that of the second resin.

[0044] Specifically, refer to Figure 3 The silver paste 40 also includes a polymer carrier, in which conductive silver powder is dispersed, together constituting the silver paste 40. The polymer carrier in the silver paste of this invention comprises a combination of a first resin and a second resin with different elastic moduli. The first resin with a high elastic modulus acts as a physical barrier to prevent water and oxygen penetration, further slowing down the migration / precipitation of silver ions. The second resin with a low elastic modulus provides excellent flexibility, improves the mechanical properties of the silver paste, optimizes the bonding, and enhances the stability and reliability of the display panel.

[0045] In some alternative embodiments of the present invention, the first resin comprises epoxy resin and / or polyimide.

[0046] In some optional embodiments of the present invention, the elastic modulus of the first resin is 2.5-40 GPa, for example, it can be 3 GPa, 5 GPa, 8 GPa, 10 GPa, 12 GPa, 15 GPa, 18 GPa, 20 GPa, 22 GPa, 25 GPa, 28 GPa, 30 GPa, 32 GPa, 35 GPa or 38 GPa, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0047] In some optional embodiments of the present invention, the elongation at break of the first resin is ≤5%, for example, it can be 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 4.8%, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0048] In some alternative embodiments of the present invention, the second resin includes any one or a combination of at least two of the following: elastomer-modified epoxy resin, polyurethane, polyurethane-modified epoxy resin, flexible epoxy resin, silicone resin, and acrylic resin.

[0049] In some optional embodiments of the present invention, the elastic modulus of the second resin is ≤3 GPa, for example, it can be 0.1 GPa, 0.2 GPa, 0.5 GPa, 0.8 GPa, 1 GPa, 1.2 GPa, 1.5 GPa, 1.8 GPa, 2 GPa, 2.2 GPa, 2.5 GPa or 2.8 GPa, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0050] In some optional embodiments of the present invention, the elongation at break of the second resin is ≥200%, for example, it can be 220%, 250%, 280%, 300%, 320%, 350%, 380%, 400%, 420%, 450%, 480%, 500%, 550%, 600%, 650%, 700%, 750% or 800%, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0051] This invention optimizes the types, elastic modulus, and elongation at break of the first and second resins. The first resin exhibits high cross-linking density, a dense structure, and low moisture absorption, acting as a physical barrier to prevent water vapor and oxygen penetration, thereby indirectly slowing down silver ion precipitation. The second resin, after curing, exhibits good flexibility and a low elastic modulus. The combination of these two resins allows the polymer carrier to fully utilize its water and oxygen barrier properties, preventing the migration and precipitation of silver ions under harsh environments such as high temperature and high humidity. This also endows the silver paste with excellent mechanical and adhesive properties, improving its bonding and electrical connection reliability under harsh conditions, resulting in higher stability and reliability for the display panel.

[0052] In some optional embodiments of the present invention, the mass of the polymer carrier is 10-50 parts, for example, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts or 45 parts, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0053] In some optional embodiments of the present invention, the mass content of the first resin in the polymer carrier is 50-80%, for example, it can be 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70%, 72%, 75% or 78%, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0054] In some optional embodiments of the present invention, the mass content of the second resin in the polymer carrier is 20-50%, for example, it can be 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45% or 48%, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0055] This invention, by designing the mass ratio of the first and second resins in the polymer carrier, effectively enhances the water and oxygen barrier function, further inhibiting the migration / precipitation of silver ions and preventing corrosion of the polarizer. Furthermore, it optimizes the mechanical and adhesive properties of the silver paste, forming a stable and reliable conductive path, preventing electrical connection failure, and ensuring the display panel maintains excellent stability and reliability under harsh environments such as high temperature and high humidity. If the ratio of the first and second resins in the polymer carrier exceeds the preferred range, the barrier and adhesive properties of the polymer carrier will decrease to varying degrees, thereby affecting the stability and reliability of the display panel under high temperature and high humidity environments.

[0056] In some optional embodiments of the present invention, the silver paste further includes a silver migration inhibitor; thereby, the migration and precipitation of silver ions can be further suppressed, preventing them from corroding the polarizer and improving the reliability of the display panel in harsh environments such as high temperature and high humidity.

[0057] Specifically, refer to Figure 3The silver paste 40 also includes a silver migration inhibitor, which, along with the conductive silver powder, is dispersed in a polymer carrier to jointly constitute the silver paste 40. In some optional embodiments of the present invention, the silver migration inhibitor includes any one or a combination of at least two of benzotriazole compounds, mercaptobenzothiazole compounds, and nitrogen-containing organic compounds; the silver migration inhibitor undergoes physical adsorption and / or weak chemical coordination with the surface of the conductive silver powder to form a monomolecular protective film, further inhibiting silver ion migration.

[0058] In some optional embodiments of the present invention, the silver migration inhibitor includes benzotriazole (BTA) and mercaptobenzothiazole (MBT). BTA forms a protective film with conductive silver powder (the conductive layer thereon) to inhibit ion migration; MBT synergistically inhibits the migration of silver ions.

[0059] In some optional embodiments of the present invention, based on 100 parts by weight of the conductive silver powder, the mass of the silver migration inhibitor is 0.1-5 parts, for example, 0.2 parts, 0.5 parts, 0.8 parts, 1 part, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.2 parts, 3.5 parts, 3.8 parts, 4 parts, 4.2 parts, 4.5 parts, or 4.8 parts, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0060] In some alternative embodiments of the present invention, the silver paste may also include other additives that are motivating to be introduced by those skilled in the art, such as any one or a combination of at least two of curing agents, dispersants, coupling agents, leveling agents, and defoamers.

[0061] In some alternative embodiments of the invention, the curing agent includes an organic amine curing agent, preferably a modified amine curing agent (e.g., an IPDA modifier), which facilitates the curing of the first resin at room temperature or medium temperature.

[0062] In some optional embodiments of the present invention, the mass of the curing agent is 0.1-8 parts, based on 100 parts of the conductive silver powder. For example, it can be 0.2 parts, 0.5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, or 7.5 parts, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0063] In some optional embodiments of the present invention, the dispersant includes a high molecular weight dispersant (such as BYK-110) which can prevent the agglomeration of conductive silver powder and improve dispersion stability.

[0064] In some optional embodiments of the present invention, the mass of the dispersant is 0.01-3 parts, based on 100 parts of the conductive silver powder. For example, it can be 0.05 parts, 0.1 parts, 0.2 parts, 0.5 parts, 0.8 parts, 1 part, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, or 2.8 parts, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0065] In some alternative embodiments of the present invention, the coupling agent includes a silane coupling agent (e.g., KH-550 and / or KH-560), which helps to improve the interfacial bonding between the polymer carrier and the conductive silver powder.

[0066] In some optional embodiments of the present invention, based on 100 parts by weight of the conductive silver powder, the mass of the coupling agent is 0.01-3 parts, for example, 0.05 parts, 0.1 parts, 0.2 parts, 0.5 parts, 0.8 parts, 1 part, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, or 2.8 parts, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0067] In some alternative embodiments of the present invention, the leveling agent includes an acrylate leveling agent, which can improve the leveling properties of the silver paste.

[0068] In some optional embodiments of the present invention, based on 100 parts by weight of the conductive silver powder, the mass of the leveling agent is 0.01-3 parts, for example, 0.05 parts, 0.1 parts, 0.2 parts, 0.5 parts, 0.8 parts, 1 part, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, or 2.8 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific point values ​​included in the range.

[0069] In some alternative embodiments of the present invention, the defoamer includes an organosilicone defoamer capable of eliminating bubbles.

[0070] In some optional embodiments of the present invention, the mass of the defoamer is 0.01-1 part, for example, 0.05 part, 0.1 part, 0.2 part, 0.5 part or 0.8 part, and specific values ​​between the above values ​​are not exhaustively listed in the present invention for the sake of space and for the sake of brevity.

[0071] In this invention, the shape of the silver paste 40 is not particularly limited. Any shape of the silver paste 40 that enables the polarizer 30 to form an electrical connection with the array substrate 10 is applicable to this invention.

[0072] In some alternative embodiments of the present invention, the shape of the silver paste includes L-shape, dot shape, or circle.

[0073] Figure 4A This is a partial structural schematic diagram of a display panel provided in another embodiment of the present invention. The direction in which the array substrate 10 points to the polarizer 30 is taken as the first direction. The silver paste 40 is flush with the side surface of the polarizer 30 away from the array substrate at the edge of the first direction.

[0074] Figure 4B This is a partial structural diagram of a display panel provided in another embodiment of the present invention. The silver paste 40 extends from the edge in the first direction to form a polarizer 30 on the side surface away from the array substrate 10. The height of the extension is ≤50μm, and can be, for example, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, 28 μm, 30 μm, 32 μm, 35 μm, 38 μm, 40 μm, 45 μm, or 48 μm, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0075] like Figure 4A and Figure 4B As shown, the edge of the silver paste 40 in the first direction is flush with or extends from the side of the polarizer 30 away from the array substrate (preferably with an extension height ≤ 50 μm). On the one hand, the silver paste 40 forms a strong and stable connection with the polarizer 30 and the array substrate 10 to ensure the reliability of the conductive path, especially to maintain the stability and reliability of the connection under harsh testing / use environments. On the other hand, it avoids pollution or local protrusion problems caused by excessive height or volume of the silver paste, so that the display panel has excellent quality and display effect.

[0076] like Figure 5 As shown, Figure 3 This is a partial structural diagram of a display panel provided in another embodiment of the present invention. The polarizer 30 can be referred to as the "upper polarizer". It is a low-resistivity polarizer, including a polarizer body 31 and a low-resistivity pressure-sensitive adhesive layer 32. The low-resistivity pressure-sensitive adhesive layer 32 is located between the polarizer body 31 and the color filter 20.

[0077] Optionally, the display panel of the present invention further includes a second polarizer 50 (also known as a "lower polarizer"), which is located on the side of the array substrate 10 opposite to the color filter 20.

[0078] Optionally, the second polarizer 50 includes a second polarizer body 51 and a pressure-sensitive adhesive layer 52, with the pressure-sensitive adhesive layer 52 located between the second polarizer body 51 and the array substrate 10.

[0079] This invention also provides a conductive silver paste, which comprises the following components by weight: 40-60 parts of conductive silver powder 10-20 parts of polymer carrier Solvent 10-40 parts; The conductive silver powder includes silver powder and a conductive layer coated on the surface of the silver powder.

[0080] The silver paste in the aforementioned display panel of the present invention is obtained by coating the conductive silver paste and curing it.

[0081] For example, in the conductive silver paste, the conductive silver powder has a mass fraction of 40-60 parts, such as 42 parts, 45 parts, 48 ​​parts, 50 parts, 52 parts, 55 parts or 58 parts, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0082] The polymer carrier has a mass fraction of 10-20 parts, for example, 11, 12, 13, 14, 15, 16, 17, 18 or 19 parts, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0083] The solvent is in the range of 10-40 parts by mass, for example, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 24 parts, 25 parts, 26 parts, 28 parts, 30 parts, 32 parts, 34 parts, 35 parts, 36 parts or 38 parts, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific values ​​included in the range.

[0084] In some optional embodiments of the present invention, the material of the conductive layer includes any one or a combination of at least two of the following: metal, metal oxide, organic conductive material, and conductive carbon material.

[0085] In some optional embodiments of the present invention, the metal includes any one or a combination of at least two of Au, Ni, Cu, Al, and Fe, preferably any one or a combination of at least two of Au, Ni, and Cu.

[0086] In some optional embodiments of the present invention, the metal oxide includes any one or a combination of at least two of copper oxide, zinc oxide, silver oxide, indium tin oxide, indium zinc oxide, fluorine-doped tin oxide, and aluminum-doped zinc oxide.

[0087] In some optional embodiments of the present invention, the organic conductive material includes a conductive polymer and / or a conductive SAM (self-assembled monolayer) material, and more preferably any one or a combination of at least two of polyaniline (PANI), poly(3,4-ethylenedioxythiophene) / poly(4-styrenesulfonate) (PEDOT / PSS), polypyrrole (PPy), and conjugated conductive SAM.

[0088] In some optional embodiments of the present invention, the conductive carbon material includes any one or a combination of at least two of conductive graphite, graphene, carbon fiber, conductive carbon black, and carbon nanotubes.

[0089] In some optional embodiments of the present invention, the thickness of the conductive layer is 1-150 nm, for example, it can be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm or 140 nm, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0090] In some optional embodiments of the present invention, the mass content of the conductive layer in the conductive silver powder is 0.5-39%, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, 32%, 34%, 35%, 36%, or 38%, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0091] In some optional embodiments of the present invention, the conductive silver powder satisfies at least one of the following conditions (1)-(4): (1) The material of the conductive layer is metal, and the thickness of the metal conductive layer in the conductive silver powder is 80-120 nm, for example, it can be 82 nm, 85 nm, 88 nm, 90 nm, 92 nm, 95 nm, 98 nm, 100 nm, 102 nm, 105 nm, 108 nm, 110 nm, 112 nm, 115 nm or 118 nm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific point values ​​included in the range.

[0092] In some optional embodiments of the present invention, the mass content of the metal conductive layer in the conductive silver powder is 23.5-38%, for example, it can be 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36% or 37%, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0093] (2) The material of the conductive layer is a metal oxide, and the thickness of the metal oxide conductive layer in the conductive silver powder is 1.5-3 nm, for example, it can be 1.6 nm, 1.8 nm, 2 nm, 2.2 nm, 2.4 nm, 2.5 nm, 2.6 nm or 2.8 nm, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0094] In some optional embodiments of the present invention, the mass content of the metal oxide conductive layer in the conductive silver powder is 1.8-3.6%, for example, it can be 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, 3%, 3.2%, 3.4% or 3.5%, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0095] (3) The material of the conductive layer is an organic conductive material. The thickness of the organic conductive layer in the conductive silver powder is 5-25 nm, for example, it can be 6 nm, 8 nm, 10 nm, 12 nm, 14 nm, 15 nm, 16 nm, 18 nm, 20 nm, 22 nm or 24 nm, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0096] In some optional embodiments of the present invention, the mass content of the organic conductive layer in the conductive silver powder is 4.6-20.5%, for example, it can be 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16%, 18% or 20%, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0097] (4) The material of the conductive layer is conductive carbon material, and the thickness of the conductive carbon material conductive layer in the conductive silver powder is 1-5 nm, for example, it can be 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm or 4.5 nm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific point values ​​included in the range.

[0098] In some optional embodiments of the present invention, the mass content of the carbon material conductive layer in the conductive silver powder is 0.8-2.4%, for example, it can be 0.9%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2% or 2.3%, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0099] In some alternative embodiments of the present invention, the polymer carrier comprises a combination of a first resin and a second resin, wherein the elastic modulus of the first resin is greater than that of the second resin.

[0100] In some alternative embodiments of the present invention, the first resin comprises epoxy resin and / or polyimide.

[0101] In some optional embodiments of the present invention, the elastic modulus of the first resin is 2.5-40 GPa, for example, it can be 3 GPa, 5 GPa, 8 GPa, 10 GPa, 12 GPa, 15 GPa, 18 GPa, 20 GPa, 22 GPa, 25 GPa, 28 GPa, 30 GPa, 32 GPa, 35 GPa or 38 GPa, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0102] In some optional embodiments of the present invention, the elongation at break of the first resin is ≤5%, for example, it can be 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 4.8%, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0103] In some alternative embodiments of the present invention, the second resin includes any one or a combination of at least two of the following: elastomer-modified epoxy resin, polyurethane-modified epoxy resin, flexible epoxy resin, polyurethane, silicone resin, and acrylic resin.

[0104] In some optional embodiments of the present invention, the elastic modulus of the second resin is ≤3 GPa, for example, it can be 0.1 GPa, 0.2 GPa, 0.5 GPa, 0.8 GPa, 1 GPa, 1.2 GPa, 1.5 GPa, 1.8 GPa, 2 GPa, 2.2 GPa, 2.5 GPa or 2.8 GPa, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0105] In some optional embodiments of the present invention, the elongation at break of the second resin is ≥200%, for example, it can be 220%, 250%, 280%, 300%, 320%, 350%, 380%, 400%, 420%, 450%, 480%, 500%, 550%, 600%, 650%, 700%, 750% or 800%, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0106] In some optional embodiments of the present invention, the mass content of the first resin in the polymer carrier is 50-80%, for example, it can be 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70%, 72%, 75% or 78%, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0107] In some optional embodiments of the present invention, the mass content of the second resin in the polymer carrier is 20-50%, for example, it can be 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45% or 48%, and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0108] In some optional embodiments of the present invention, the solvent includes ether solvents, preferably ethylene glycol ether solvents and / or propylene glycol ether solvents. The solvent has the characteristic of fast drying, enabling it to quickly evaporate after coating, allowing the conductive silver paste to solidify and form a silver paste structure, and also has the effect of inhibiting the release of silver ions.

[0109] For example, the ethylene glycol ether solvent includes any one or a combination of at least two of ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol butyl ether, diethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol butyl ether, ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, and diethylene glycol butyl ether acetate.

[0110] For example, the propylene glycol ether solvent includes any one or a combination of at least two of propylene glycol methyl ether, dipropylene glycol methyl ether, propylene glycol methyl ether acetate, and dipropylene glycol methyl ether acetate.

[0111] In some optional embodiments of the present invention, the solvent includes propylene glycol methyl ether acetate (PMA) and ethylene glycol butyl ether (BCS), wherein propylene glycol methyl ether acetate serves as the main solvent, capable of dissolving the polymer carrier and adjusting the viscosity; and ethylene glycol butyl ether serves as a co-solvent, capable of adjusting the evaporation gradient.

[0112] In some optional embodiments of the present invention, the conductive silver paste further includes 0.1-2 parts by weight of silver migration inhibitor, for example, 0.2 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.8 parts, 1 part, 1.2 parts, 1.4 parts, 1.5 parts, 1.6 parts or 1.8 parts, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0113] In some optional embodiments of the present invention, the silver migration inhibitor includes any one or a combination of at least two of benzotriazole compounds, mercaptobenzothiazole compounds, and nitrogen-containing organic compounds.

[0114] In one alternative embodiment, the silver migration inhibitor comprises benzotriazole (BTA) and mercaptobenzothiazole (MBT). BTA forms a protective film with conductive silver powder (the conductive layer thereon) to inhibit ion migration; MBT synergistically inhibits the migration of silver ions.

[0115] It should be noted that the conductive silver paste also includes other additives that are beneficial to processing and that are of motivation to be added by those skilled in the art. These other additives include any one or a combination of at least two of the following: curing agents, dispersants, coupling agents, leveling agents, and defoamers.

[0116] In some alternative embodiments of the invention, the curing agent comprises an organic amine curing agent, preferably a modified amine curing agent (e.g., an IPDA modifier), which facilitates the curing of the polymer carrier (especially the first resin, such as an epoxy resin) at room temperature or medium temperature.

[0117] In some optional embodiments of the present invention, the conductive silver paste further includes 1-5 parts of curing agent by weight, for example, 1.2 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts or 4.5 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific point values ​​included in the range.

[0118] In some optional embodiments of the present invention, the dispersant includes a high molecular weight dispersant (such as BYK-110) which can prevent the agglomeration of conductive silver powder and improve dispersion stability.

[0119] In some optional embodiments of the present invention, the conductive silver paste further includes 0.01-5 parts of dispersant by weight, for example, 0.05 parts, 0.1 parts, 0.2 parts, 0.5 parts, 0.8 parts, 1 part, 1.2 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts or 4.5 parts, as well as specific values ​​between the above-mentioned values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0120] In some alternative embodiments of the present invention, the coupling agent includes a silane coupling agent (e.g., KH-550 and / or KH-560), which helps to improve the interfacial bonding between the polymer carrier and the conductive silver powder.

[0121] In some optional embodiments of the present invention, the conductive silver paste further includes 0.01-3 parts by weight of coupling agent, for example, 0.05 parts, 0.1 parts, 0.2 parts, 0.5 parts, 0.8 parts, 1 part, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts or 2.8 parts, as well as specific values ​​between the above-mentioned values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0122] In some alternative embodiments of the present invention, the leveling agent includes an acrylate leveling agent, which can improve the coating leveling properties of the conductive silver paste.

[0123] In some optional embodiments of the present invention, the conductive silver paste further includes 0.01-3 parts by weight of leveling agent, for example, 0.05 parts, 0.1 parts, 0.2 parts, 0.5 parts, 0.8 parts, 1 part, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts or 2.8 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific point values ​​included in the range.

[0124] In some alternative embodiments of the present invention, the defoamer includes an organosilicon defoamer, which is capable of eliminating bubbles generated during the preparation, stirring and coating of conductive silver paste.

[0125] In some optional embodiments of the present invention, the conductive silver paste further includes 0.01-1 parts of defoamer by weight, for example, 0.05 parts, 0.1 parts, 0.15 parts, 0.2 parts, 0.5 parts or 0.8 parts, as well as specific values ​​between the above-mentioned values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0126] In one embodiment, the conductive silver paste comprises the following components by weight: 40-60 parts of conductive silver powder 7-10 parts epoxy resin, 4-10 parts of the second resin, 2-5 parts of hardener 10-20 parts of propylene glycol methyl ether acetate 2-10 parts of ethylene glycol butyl ether Benzotriazole 0.1-0.5 parts, 0.1-0.3 parts of mercaptobenzothiazole, Dispersant 0.1-1 part, 0.1-1 part of silane coupling agent, Leveling agent 0.1-0.5 parts, 0.05-0.2 parts of defoamer.

[0127] Preferably, the conductive silver powder is spherical silver powder coated with a copper conductive layer to provide conductivity. The epoxy resin, as the rigid first resin, is preferably a bisphenol A type epoxy resin with high modulus and high glass transition temperature (T0). gThe epoxy resin exhibits high adhesion and excellent chemical resistance; the proportions of the epoxy resin can be 7.5 parts, 8 parts, 8.5 parts, 9 parts, or 9.5 parts, etc. The second resin is a polyurethane-modified epoxy resin and / or a flexible epoxy resin, a soft resin with a low elastic modulus, possessing toughening, impact resistance, and bending resistance properties; the proportions of the second resin can be 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, or 9.5 parts, etc. The curing agent is an organic amine curing agent, preferably a modified amine curing agent (e.g., IPDA modifier), which helps to achieve curing of the epoxy resin at room temperature or medium temperature. The propylene glycol methyl ether acetate serves as the main solvent, capable of dissolving the resin and adjusting viscosity; its component amounts can be 12, 14, 15, 16, or 18 parts. The ethylene glycol butyl ether serves as a co-solvent, capable of adjusting the volatility gradient; its component amounts can be 3, 4, 5, 6, 7, 8, or 9 parts. Benzotriazole (BTA) and mercaptobenzothiazole (MBT) serve as silver migration inhibitors. BTA forms a protective film with the conductive silver powder (and its conductive layer), inhibiting ion migration; its component amounts can be 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, or 0.45 parts. MBT synergistically inhibits silver ion migration; its component amounts can be 0.15, 0.2, or 0.25 parts. The dispersant is a high molecular weight dispersant (such as BYK-110), which can prevent the conductive silver powder from agglomerating and improve dispersion stability. The silane coupling agent (e.g., KH-550 and / or KH-560) helps improve the interfacial bonding between the resin and the conductive silver powder. The leveling agent is an acrylate leveling agent, which can improve the coating leveling properties of the conductive silver paste. The defoamer is an organosilicone defoamer, used to eliminate bubbles generated during stirring and coating of the conductive silver paste.

[0128] This invention also provides a method for preparing the conductive silver paste described in the foregoing embodiments, the method comprising: mixing conductive silver powder, polymer carrier and solvent uniformly to obtain the conductive silver paste.

[0129] In some optional embodiments of the present invention, the conductive silver powder is prepared by any of the following methods: chemical deposition, deposition oxidation, magnetron sputtering, or in-situ polymerization.

[0130] In some optional embodiments of the present invention, the conductive layer is made of metal, and the conductive silver powder can be prepared by chemical deposition.

[0131] In one specific embodiment, the method for preparing the conductive silver powder includes: activating the silver powder and then placing it in a plating solution for chemical deposition to obtain the conductive silver powder.

[0132] For example, the conductive layer is made of copper (Cu), and the conductive silver powder is prepared by chemical deposition (chemical copper plating process), including the following steps: S11. Degrease the silver powder with alkali (preferably under gentle boiling conditions, for 10-15 minutes), and then rinse with water. S12. The sample obtained in S11 is acid-washed and activated (preferably for 2-5 seconds) to remove the oxide layer, and then rinsed with water until neutral. If an organic modified layer is present, it shall be cleaned by ultrasonic boiling in boiling water (preferably 10-40 min, for example 30 min, with an ultrasonic power of 200 W) and / or ultrasonic boiling in ethanol (preferably 10-40 min, for example 30 min, with an ultrasonic power of 200 W). After cleaning, the sample should be thoroughly dried (preferably under vacuum or N2 protection, at 70-90°C for 1-36 h, preferably 2-24 h, for example, at 80°C for 24 h). S13. Prepare a chemical copper plating solution, including CuSO4 (or its hydrate), EDTA-2Na, NaOH and formaldehyde; For example, the composition of the electroless copper plating solution is as follows: CuSO4·5H2O (main salt) 15 g / L, EDTA-2Na (complexing agent) 50 g / L, formaldehyde (37% aqueous solution, reducing agent) 15 mL / L, NaOH (pH adjuster) 12 g / L, 2,2'-bipyridine (stabilizer) 40 mg / L, potassium ferrocyanide 15 mg / L, PEG-6000 (polyethylene glycol, dispersant) 0.3 g / L; the pH value of the electroless copper plating solution is 12.5.

[0133] The sample obtained in step S12 is placed in the electroless copper plating solution (e.g., loading amount of 10 g / L silver powder) and chemically deposited at 50-65°C with continuous stirring for 0.5-4 h (e.g., 50°C, stirring speed of 400 rpm, time of 30 min). S14. Clean the sample obtained in step S13 (e.g., use water to ultrasonically clean 3 times, 5-10 min each time; then clean with ethanol), and dry it (preferably vacuum dry, 60-80℃) to obtain conductive silver powder with copper conductive layer.

[0134] In some optional embodiments of the present invention, the material of the conductive layer is a metal oxide, and the conductive silver powder can be prepared by deposition oxidation method.

[0135] In one specific embodiment, the method for preparing the conductive silver powder includes: activating the silver powder and then placing it in a plating solution for chemical deposition, followed by oxidation to obtain the conductive silver powder.

[0136] For example, the conductive layer is made of copper oxide, and the conductive silver powder is prepared by a deposition oxidation method (chemical passivation process), including the following steps: S21. Degrease the silver powder with alkali (preferably under gentle boiling conditions, for 10-15 minutes), and then rinse with water. S22. The sample obtained in step S21 is acid-washed and activated (preferably for 2-5 min), and then rinsed with water until neutral. Dry the cleaned sample thoroughly (preferably under vacuum or N2 protection, at 70-90℃ for 12-36 h, for example at 80℃ for 24 h). S23. Prepare a chemical copper plating solution, including CuSO4, EDTA-2Na, NaOH and formaldehyde; The sample obtained in step S22 was placed in the electroless copper plating solution and chemically deposited for 2-4 hours under continuous stirring at 60-65°C. S24. Clean the sample obtained in step S23 (preferably, ultrasonically clean with water 3 times, 5-10 min each time; then clean with ethanol), and dry (preferably vacuum dry, 60-80℃). S25. The sample obtained in step S24 is subjected to oxidation treatment. The oxidation treatment method includes thermal oxidation treatment (air atmosphere, preferably 200-300℃, 2-4 h) or liquid phase oxidation treatment (NaOH / NaNO2 system, preferably 60-80℃, 1-2 h) to oxidize the chemically deposited metal and form metal oxides. S26. The sample obtained in step S25 is cleaned, dried and packaged to obtain conductive silver powder with copper oxide as the conductive layer.

[0137] In one embodiment, the prepared conductive silver powder containing copper or copper oxide as a conductive layer was tested using a scanning electron microscope (SEM), and its elemental composition was determined using an energy dispersive spectroscopy (EDS) instrument. The resulting EDS image is shown below. Figure 6 As shown, this indicates that the conductive silver powder contains Cu.

[0138] In some optional embodiments of the present invention, the material of the conductive layer is an organic conductive material, and the conductive silver powder can be prepared by in-situ polymerization.

[0139] In one specific embodiment, the conductive layer is made of a conductive polymer, and the method for preparing the conductive silver powder includes: activating the silver powder and then placing it in a monomer solution for polymerization reaction to obtain the conductive silver powder.

[0140] For example, the conductive layer is made of polyaniline, and the conductive silver powder is prepared by in-situ polymerization, including the following steps: S31. Remove the oil from the silver powder by alkaline washing (e.g., NaOH / Na2CO3 / Na3PO3, preferably under gentle boiling conditions, for 10-15 minutes), and then rinse with water. S32. The sample obtained in step S31 is acid-washed and activated (e.g., hydrochloric acid solution, preferably 0.5-1.5 M, such as 1 M hydrochloric acid solution, at room temperature, preferably 2-5 min), and then rinsed with water until neutral. S33. Disperse the sample obtained in step S32 in ethanol by ultrasonication (preferably 10-60 min, for example 30 min). S34. Prepare aniline monomer solution and APS (ammonium persulfate) solution, and pre-cool in an ice-water bath; The sample obtained in step S33 is added to the aniline monomer solution under N2 protection, and then APS solution is slowly added dropwise (preferably 10-30 mL / h, 2-20 h, for example 20 mL / h, about 8 h); the reaction is continued under stirring at 0-25°C until the polymerization endpoint (preferably 10-36 h, for example 24 h). S35. Filter the sample obtained in step S34, then wash it with HCl, wash it with water, and dry it (preferably vacuum dry at 50-80℃ for 24-48 h, for example, vacuum dry at 60℃ for 24-48 h) to obtain conductive silver powder with polyaniline as the conductive layer.

[0141] In some optional embodiments of the present invention, the conductive layer is made of conductive carbon material, and the conductive silver powder can be prepared by magnetron sputtering.

[0142] For example, the conductive layer is made of conductive carbon material, and the method for preparing the conductive silver powder includes the following steps: S41. Remove the silver powder by alkaline washing (e.g., NaOH / Na2CO3 / Na3PO3, preferably under gentle boiling conditions, 10-15 min), and then rinse with water (preferably 3 times). S42. The sample obtained in step S41 is acid-washed and activated (e.g., hydrochloric acid solution, room temperature, preferably 2-5 min), and then rinsed with water until neutral. S43. Disperse the sample obtained in step S42 in ethanol by ultrasonication (preferably 10-60 min, for example 30 min), and then dry it (preferably vacuum drying or drying under N2 protection, 60-80℃, 12-24 h). S44. Load the sample obtained in step S43 into the powder sputtering chamber and evacuate to a vacuum level of ≤4×10⁻⁶. -3Pa; Introduce Ar gas and adjust the working pressure to 1-5 Pa; First, perform sputtering (baffle shielding, clean the target surface, 5-10 min); Then, perform formal sputtering (preferably continuous powder rotation + intermittent vibration), with an RF power of 50-200 W and a time of 0.5-2 h; Turn off the power, stop the gas supply, cool to room temperature, remove the sample, vacuum seal and preserve it to obtain conductive silver powder with a conductive carbon material as the conductive layer.

[0143] In one embodiment, the conductive silver paste is prepared as follows: S51. Resin pretreatment: The first and second resins are preheated at 40-50℃ to reduce viscosity and facilitate subsequent mixing; then vacuum degassing (pressure ≤ -0.095 MPa, 30 min) is performed to remove dissolved gases. S52. Mix the pretreated first resin, second resin, conductive silver powder, solvent, optional silver migration inhibitor, and optional other additives (e.g., any one or at least two combinations of curing agent, dispersant, coupling agent, leveling agent, and defoamer) according to the formulation amount, and then perform planetary stirring according to the following procedure: control the temperature at 25±2℃ to prevent solvent evaporation; maintain a vacuum of -0.08 MPa to reduce air bubble incorporation; first, stir at low speed (30 rpm rotation, 50 rpm revolution) for initial wetting and dispersion; then stir at high speed (60 rpm rotation, 100 rpm revolution) to achieve uniform dispersion. S53. The material obtained in step S52 is ground using a three-roll mill. The first roller spacing is 25 / 15 / 5 μm, and the discharge temperature is ≤35℃. It is used to achieve coarse grinding and dispersion with a fineness target of ≤15 μm. The second roller spacing is 15 / 8 / 3 μm, and the discharge temperature is ≤30℃. It is used to achieve fine grinding and refinement with a fineness target of ≤10 μm. S54. The material obtained in step S53 is subjected to vacuum degassing, and the vacuum degree is controlled to be ≤-0.098 MPa. At the same time, the vacuum is broken once every 10 minutes to assist in degassing and accelerate the rise of bubbles; let it stand for 2-4 hours to stabilize the viscosity. S55. Filter and package the material obtained in step S54 to obtain conductive silver paste.

[0144] A display panel is prepared using the conductive silver paste provided in this embodiment of the invention, wherein the display panel includes an array substrate, a color filter and a polarizer, the color filter is located between the array substrate and the polarizer, and the polarizer and the array substrate are electrically connected by silver paste; the silver paste is obtained by curing the conductive silver paste.

[0145] The display panel of the embodiment underwent aging verification, testing the silver paste penetration and corrosion after THBS 65℃ / 93%RH for 1500 h. The test results are shown in the figure below. Figure 8 As shown, the maximum corrosion diffusion distance (max) of the CFOG region is 267 μm, and the maximum corrosion diffusion distance of the MOD region is 547 μm, which is significantly better than the specification requirement (maximum corrosion diffusion distance 1500 μm), indicating that the display panel provided by the present invention has excellent resistance to damp heat and reliability.

[0146] Therefore, this invention, by designing a conductive layer in the conductive silver powder, enables the silver paste to have excellent conductivity while effectively suppressing the migration and precipitation of silver ions under harsh environments such as high temperature and high humidity. This avoids corrosion problems caused by the reaction of silver ions with iodine ions in the polarizer, giving the display panel higher resistance to damp heat and stability and reliability, and improving the display quality and yield of the product.

[0147] Furthermore, the present invention preferably uses a high elastic modulus first resin and a low elastic modulus second resin as a polymer carrier for the silver paste. Through the combined action of the two types of resins, the water and oxygen barrier effect can be fully utilized to prevent the migration and precipitation of silver ions in harsh environments such as high temperature and high humidity, and to give the silver paste excellent mechanical and adhesive properties, so that the display panel has higher stability and reliability.

[0148] Comparative Example A display panel prepared using existing silver paste technology is used as a comparative example. The comparative example display panel includes an array substrate, a color filter, and a polarizer. The color filter is located between the array substrate and the polarizer. The polarizer and the array substrate are electrically connected by silver paste. The silver paste is obtained by curing conventional silver paste.

[0149] A proportional display panel was subjected to aging verification, testing the silver paste penetration and corrosion after THBS 65℃ / 93%RH for 1500 h. The test results are shown in the figure below. Figure 9 As shown, the maximum corrosion diffusion distance (max) in the CFOG region is 4600 μm, and the maximum corrosion diffusion distance in the MOD region is 3148 μm, indicating a significant lack of product reliability. This demonstrates that in existing silver pastes, the silver powder is not coated or modified. Under high temperature and humidity conditions, silver ions migrate and precipitate, reacting with iodine ions in the polarizer, leading to severe corrosion defects in the display panel and affecting product reliability and display performance.

[0150] This invention also provides a display device, which includes a display panel as described in any of the foregoing embodiments.

[0151] Since the display device uses the aforementioned display panel, it also possesses the technical effects of the display panel described in the above embodiments. It should be noted that the display device provided in this embodiment may also include other circuits and devices for supporting the normal operation of the display device. The display device exemplarily includes, but is not limited to, an in-vehicle liquid crystal display device.

[0152] The present invention has been illustrated through the above embodiments, but the present invention is not limited to the above process steps, that is, it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials used in the present invention, additions of auxiliary components, and selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A display panel, characterized in that, The display panel includes an array substrate, a color filter, and a polarizer. The color filter is located between the array substrate and the polarizer, and the polarizer and the array substrate are electrically connected by silver paste. The silver paste includes conductive silver powder, which comprises silver powder and a conductive layer coated on the surface of the silver powder.

2. The display panel according to claim 1, characterized in that, The material of the conductive layer includes any one or a combination of at least two of the following: metal, metal oxide, organic conductive material, and conductive carbon material. And / or, the thickness of the conductive layer is 1-150 nm; And / or, the mass content of the conductive layer in the conductive silver powder is 0.5-39%.

3. The display panel according to claim 1, characterized in that, The conductive silver powder satisfies at least one of the following conditions (1)-(4): (1) The material of the conductive layer is metal, and the thickness of the metal conductive layer in the conductive silver powder is 80-120 nm, and the mass content is 23.5-38%; (2) The material of the conductive layer is a metal oxide, and the thickness of the metal oxide conductive layer in the conductive silver powder is 1.5-3 nm, and the mass content is 1.8-3.6%; (3) The material of the conductive layer is an organic conductive material, and the thickness of the organic conductive layer in the conductive silver powder is 5-25 nm, and the mass content is 4.6-20.5%; (4) The conductive layer is made of conductive carbon material, and the thickness of the conductive carbon material conductive layer in the conductive silver powder is 1-5 nm, and the mass content is 0.8-2.4%.

4. The display panel according to claim 1, characterized in that, The silver paste also includes a polymer carrier, which comprises a combination of a first resin and a second resin, wherein the elastic modulus of the first resin is greater than that of the second resin.

5. The display panel according to claim 4, characterized in that, The first resin includes epoxy resin and / or polyimide; And / or, the elastic modulus of the first resin is 2.5-40 GPa; And / or, the elongation at break of the first resin is ≤5%; And / or, the second resin includes any one or a combination of at least two of the following: elastomer-modified epoxy resin, polyurethane, polyurethane-modified epoxy resin, flexible epoxy resin, silicone resin, and acrylic resin. And / or, the elastic modulus of the second resin is ≤3 GPa; And / or, the elongation at break of the second resin is ≥200%.

6. The display panel according to claim 4, characterized in that, Based on 100 parts by weight of the conductive silver powder, the polymer carrier has a mass of 10-50 parts. And / or, the polymer carrier contains 50-80% by mass of the first resin and 20-50% by mass of the second resin.

7. The display panel according to claim 1, characterized in that, The silver paste also includes silver migration inhibitors.

8. The display panel according to claim 7, characterized in that, The silver migration inhibitors include any one or a combination of at least two of the following: benzotriazole compounds, mercaptobenzothiazole compounds, and nitrogen-containing organic compounds; And / or, based on 100 parts by weight of the conductive silver powder, the mass of the silver migration inhibitor is 0.1-5 parts.

9. The display panel according to claim 1, characterized in that, The shape of the silver paste includes L-shape, dot shape, or circle.

10. The display panel according to claim 1, characterized in that, With the direction of the array substrate pointing towards the polarizer as the first direction, the edge of the silver paste in the first direction is flush with the surface of the polarizer on the side away from the array substrate. Alternatively, the silver paste extends from the edge of the polarizer in the first direction to the side surface away from the array substrate, and the height of the extension is ≤50 μm.

11. A conductive silver paste, characterized in that, The conductive silver paste comprises the following components in parts by weight: 40-60 parts of conductive silver powder 10-20 parts of polymer carrier Solvent 10-40 parts; The conductive silver powder includes silver powder and a conductive layer coated on the surface of the silver powder.

12. The conductive silver paste according to claim 11, characterized in that, The material of the conductive layer includes any one or a combination of at least two of the following: metal, metal oxide, organic conductive material, and conductive carbon material. And / or, the thickness of the conductive layer is 1-150 nm; And / or, the mass content of the conductive layer in the conductive silver powder is 0.5-39%.

13. The conductive silver paste according to claim 11, characterized in that, The conductive silver powder satisfies at least one of the following conditions (1)-(4): (1) The material of the conductive layer is metal, and the thickness of the metal conductive layer in the conductive silver powder is 80-120 nm, and the mass content is 23.5-38.0%; (2) The material of the conductive layer is a metal oxide, and the thickness of the metal oxide conductive layer in the conductive silver powder is 1.5-3 nm, and the mass content is 1.8-3.6%; (3) The material of the conductive layer is an organic conductive material, and the thickness of the organic conductive layer in the conductive silver powder is 5-25 nm, and the mass content is 4.6-20.5%; (4) The conductive layer is made of conductive carbon material, and the thickness of the conductive carbon material conductive layer in the conductive silver powder is 1-5 nm, and the mass content is 0.8-2.4%.

14. The conductive silver paste according to claim 11, characterized in that, The polymer carrier comprises a combination of a first resin and a second resin, wherein the elastic modulus of the first resin is greater than that of the second resin.

15. The conductive silver paste according to claim 14, characterized in that, The first resin includes epoxy resin and / or polyimide; And / or, the elastic modulus of the first resin is 2.5-40 GPa; And / or, the elongation at break of the first resin is ≤5%; And / or, the second resin includes any one or a combination of at least two of the following: elastomer-modified epoxy resin, polyurethane-modified epoxy resin, flexible epoxy resin, polyurethane, silicone resin, and acrylic resin. And / or, the elastic modulus of the second resin is ≤3 GPa; And / or, the elongation at break of the second resin is ≥200%; And / or, the polymer carrier contains 50-80% by mass of the first resin and 20-50% by mass of the second resin.

16. The conductive silver paste according to claim 11, characterized in that, The solvents include ethylene glycol ether solvents and / or propylene glycol ether solvents.

17. The conductive silver paste according to claim 11, characterized in that, The conductive silver paste also includes 0.1-2 parts by weight of silver migration inhibitor; And / or, the silver migration inhibitors include any one or a combination of at least two of benzotriazole compounds, mercaptobenzothiazole compounds, and nitrogen-containing organic compounds.

18. A method for preparing conductive silver paste according to any one of claims 11-17, characterized in that, The preparation method includes: mixing conductive silver powder, polymer carrier and solvent evenly to obtain the conductive silver paste.

19. The preparation method according to claim 18, characterized in that, The conductive silver powder is prepared by any of the following methods: chemical deposition, deposition oxidation, magnetron sputtering, or in-situ polymerization.

20. A display device, characterized in that, The display device includes a display panel as described in any one of claims 1-10.